(untitled) (Journal for Studies in Humanities and Social Sciences, 2018)
The main aim of this article is to explore the sexual challenges (khaedu dza vhudzekani) divorcees face as they relate to pastoral care and counselling in the church. The objectives of the study were (1) to identify and describe the sexual challenges of divorcees as they relate to pastoral care and counselling in the Reformed Churches of South Africa within the Vhembe District, and (2) to contribute towards the development of an African-orientated approach to pastoral care and counselling to sup-port the Vhavenda divorcees with challenges (khaedu dza vhudzekani) after the pain of divorce and this challenge affects their faith and their practical lives. This study argues that caring and counsel-ling for divorcees should be one of the primary missions of the church. The case study involved believers who are members of the Reformed Churches of South Africa: Synod Soutpansberg, particularly the churches that minister to the Vhavenda people in the Vhembe District Municipality in the Limpopo Province in South Africa. The research employed a qualitative method, with triangulation of data as a method to validate the data collection. The findings of this study show that divorcees experience many sexual challenges, and that Reformed pastors are not doing enough to address those challenges. The findings and recommendations of the study could be useful in guiding pastors in providing pastoral care and counselling to divorcees. The article proposes a new approach of supporting church members who divorcees and who are experiencing sexual challenges.